Perbandingan Hasil Pemeriksaan Asam Urat Metode Point of Care Testing (POCT) dengan Metode Fotometrik - Agus Sudrajat; Muhammad Anwar Fuady (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The techniques used in laboratory examinations are crucial for diagnosing illnesses, including figuring out how much uric acid is in the body. The photometric technique and the Point Of Care Testing (POCT) approach are two of them. The aim of this research is to examine the findings of uric acid level examinations in persons between the ages of 20 and 40 in families and communities in Ciparay District, Bandung Regency, using POCT and photometric techniques. This is a cross-sectional research that employs a sequential random sample approach on 30 populations for sampling. A normality test utilizing the Paired Sample T-Test and the One-Sample Kolmogorov-Smirnov Test was used to analyze the data. The analysis's findings revealed that the uric acid level determined by the photometric technique was 4,920±1,480, whereas the average and standard deviation for the POCT method was 5,266±1,439. This indicates that the two approaches' average uric acid levels differ from one another. With a p-value of 0.045, the paired T-test demonstrated a significant difference between the photometric and POCT methods.